The Effect of Promotion on Purchase Decisions Through Purchase Intentions as an Intervening Variable on Kopi Kenangan Merak in Samarinda - Mariana, Viera; Istimaroh, Istimaroh (Research in Management of Technology and Business, 2024)
Researchers found that with the increasing competition in the culinary industry, Café Kopi Kenangan must maintain its marketing strategy to develop promotions and maximize its market potential. The purpose of this study was to determine how promotion affects purchasing decisions through purchase intention as a mediating variable at Café Kopi Kenangan Merak in Samarinda. The population in this study were customers who had made purchases at Café Kopi Kenangan Merak in Samarinda. This study uses quantitative descriptive methods. The sample used in this study was 213 participants who were taken by nonprobability sampling method using accidental sampling. This study collects data using a questionnaire that can be accessed via a Google Form link. SmartPLS version 4.02 was used to process the data. The results in this study indicate that promotion has a positive and significant effect on purchasing decisions, promotion has a positive and significant effect on buying interest, buying interest has a positive and significant impact on purchasing decisions, promotion has a positive and significant impact on purchasing decisions through buying interest as a mediating variable. With various promotions, it is expected to be able to attract and retain customers. Based on these findings, it is recommended that the cafe can schedule promotions via social media in a structured manner so that customers can enjoy it when visiting the cafe.